Content valuation strategies for digital subscription platforms - Raoul Kübler; Rouven Seifert; Michael Kandziora (Journal of Cultural Economics, 2020)
For digital video subscription platforms, creating and managing content portfolios are critical to acquire new customers, retain existing customers, leverage cross-sales, and generate advertising revenues. We treat content portfolios as a form of pure bundling which may vary in composition and attractiveness over time. Therefore, evaluating the value contribution of each content piece is essential to manage a platform's portfolio efficiently and to understand how a specific content piece contributes to the bundle's attractiveness. In this article, we develop an ROI content valuation framework for a digital film subscription platform. This framework describes how a single piece of content diffuses through consumers' journeys and influences subscription fees through acquisition and retention as well as revenues from cross-sales and advertising. This conceptual approach allows us to address the heterogeneity across content and platform contingencies such as exclusive availability and platform specifics, and link them to revenue streams. Building on this framework, we offer avenues for future research and provide potential lead performance indicators together with their operationalization, enabling all parties involved in the production, marketing, distribution, and sales of content to determine the platform-specific value of a content piece.
Keywords: L82; M21; M30; M31; 330; Video on demand; Business models; Content strategy; Portfolio valuation